Progress in Nanophotonics 3 - Ohtsu, Motoichi; Yatsui, Takashi (Nano-Optics and Nanophotonics, 2015)
This book focuses on the recent progress in nanophotonics technology to be used to develop novel nano-optical devices, fabrication technology and advanced systems. It reviews light-emitting diodes and lasers made of silicon bulk crystals in which the light emission principle is based on dressed-photon-phonons. Further topics include: theoretical studies of optoelectronic properties of molecular condensates for organic solar cells and light-emitting devices, the basics of topological light beams together with their important properties for laser spectroscopy, spatially localized modes emerging in nonlinear discrete dynamic systems and theoretical methods to explore the dynamics of nanoparticles by the light-induced force of tailored light fields under thermal fluctuations. These topics are reviewed by leading scientists. This overview is a variable resource for engineers and scientists working in the field of nanophotonics.